PENGARUH BUDAYA ORGANISASI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT FASTFOOD INDONESIA Tbk. (KFC CABANG DEMANG LEBAR DAUN) PALEMBANG - Firdaus Sianipar; Dwi Karsasih; Sri Murniati (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
ABSTRACTThe Effect of Organizational Culture and Communication on Employee Performance at PT.Fastfood Indonesia Tbk. (KFC Demang Lebar Daun branch) Palembang with a population of 59 employees, the sample in this study was a saturated sample. The data collection technique was carried out through questionnaire distribution and processed statistically using the multiple regression analysis method with Y = a + b1 X1 + b2X2 + e processed with the SPSS program 17. From the results of the validity test obtained r count> r table for each item statement and the reliability test questionnaire obtained the value of each variable which is 0.757 for variable X1, 0.771 for variable X2, and 0.765 for variable Y. The value explains the value of reliability> 0.60, meaning that the value of research instruments are reliable and can be used as a measuring instrument analyzed further. Data analysis of each variable obtained by the multiple linear regression equation Y = 6.694 + 0.313 X1 + 0.732 X2 + e. Obtained R Square value of 0.410, which means X1 and X2 explain the effect on the Y variable by 41%, while the remaining 59% is explained by other variables outside the study. From the results of the calculation of simultaneous test as large as 21,166 with F table of 3.16 which means Fcount> F table with a significant value of 0.005, which means that Organizational Culture and communication together influence simultaneously on the performance of employees at the KFC Demang Lebar Daun Palembang branch. From the partial test generated, each independent variable has a significant effect on the dependent variable, with Organizational Culture having a significance level of less than 0.05 so that the hypothesis is accepted while the Communication variable also has a significance of research smaller than 0.005 so that the hypothesis is accepted. Keywords: Organizational Culture, Communication, and Performance